Sisa Lebih Perhitungan Anggaran (SiLPA) Pada Anggaran Pendapatan dan Belanja Daerah (APBD) Kabupaten Batang Hari - Rosmawati, Sri; Muryati, Muryati (Universitas Batanghari Jambi, 2024)
SiLPA is the remaining budget formed the financial management process in terms of regional revenue and terms of regional expenditure. SiLPA can occur as a result of exceeding PAD receipts, exceeding financing receipts, spending savings, obligations to third parties until the end of the year that have not been resolved and remaining funds due The purpose of this study is to determine the condition of SiLPA in Batang Hari Regency and the components that cause SiLPA in the 2017-2022 fiscal year. The research method used in this study is Descriptive Quantitative, describing the components estimated to trigger the occurrence of SiLPA. to non-achievement of performance targets and remaining financing expenditure funds. Based on the results, it can be concluded that the SiLPA of Batang Hari Regency occurs on average due to savings in regional spending. This can be compared to the regional revenue of Batang Hari Regency which on average does not exceed the APBD target during the 2017-2022 fiscal year period.